Multiple Modes of Delivery. - Smith, Andy; Hill, Doug; Ling, Peter (Australian Universities Teaching Committee, 2005)
Final report of a study investigating the factors affecting universities when setting priorities in relation to educational delivery, and the means by which they achieve the most effective combination of methodologies. The researchers examined the way in which selected Australian universities have expanded their options for educational delivery, and explores: the issues of development, implementation and evaluation of both established and innovative modes of delivery; and the establishment of an appropriate balance of methodologies to meet both pedagogical and organisational requirements in various circumstances. The project also considers the general socio-economic environment in which low skill/ low pay jobs are disappearing and high skill high pay positions are increasing in response to globalisation, and the subsequent changes in expectations of both government and employers.